2003
DOI: 10.1038/sj.bjc.6601173
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in apoptosis and proliferation following primary chemotherapy for breast cancer

Abstract: Patients undergoing primary chemotherapy for invasive breast cancer consented to a core biopsy of the invasive breast primary preand 24 h postchemotherapy. The resulting tissue was analysed for apoptosis, Ki67, ER and HER-2 using immunohistochemical techniques. These data were then used to evaluate the relationship between these biological markers and response to chemotherapy and overall survival. Response rate to chemotherapy in this group was 86%, 16 patients (25%) achieved a clinical complete response and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
62
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 42 publications
10
62
0
1
Order By: Relevance
“…However, investigations that have studied the importance of apoptosis in human solid tumors have been sparse. Studies of cervical cancer have found the baseline apoptotic index of the malignant cells to be prognostic of clinical response to chemotherapy (26) and overall survival (27). The determination of baseline apoptotic index in breast cancer has been investigated but without definitive indication on the appropriate therapeutic implications of these information (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, investigations that have studied the importance of apoptosis in human solid tumors have been sparse. Studies of cervical cancer have found the baseline apoptotic index of the malignant cells to be prognostic of clinical response to chemotherapy (26) and overall survival (27). The determination of baseline apoptotic index in breast cancer has been investigated but without definitive indication on the appropriate therapeutic implications of these information (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of cervical cancer have found the baseline apoptotic index of the malignant cells to be prognostic of clinical response to chemotherapy (26) and overall survival (27). The determination of baseline apoptotic index in breast cancer has been investigated but without definitive indication on the appropriate therapeutic implications of these information (26,27). Therefore, determining the importance of therapy-induced apoptosis in solid tumors currently remains a relatively unexplored area of clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that the tumour morphology after treatment will be determined by factors in addition to proliferation, such as cell loss. In this respect, although Ki67 is a primary marker of proliferation, it can also be a secondary reflection of cell death (Archer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies have produced partially conflicting results, it is apparent that higher pre-therapy proliferation is associated with a better response and that a significant fall in Ki67 occurs following neoadjuvant chemotherapy [6,7]. We have previously shown for neoadjuvant endocrine therapy, that Ki67 assessment performed in samples already exposed to therapy more accurately predicts outcome than its assessment in pretherapy biopsies, but this is not known for chemotherapy [8].…”
Section: Introductionmentioning
confidence: 99%